'My biggest fear was whether or not I would make friends': working-class students' reflections on their transition to university in Ireland. Issue 6 (2nd July 2020) - Scanlon, Margaret; Leahy, Pat; Jenkinson, Hilary; Powell, Fred
ABSTRACT: Over the last few decades there has been increased recognition that the concept of 'access' encompasses not only entry to higher education (HE) but also participation and successful completion. Despite this, very little research has been carried out in Ireland on non-traditional students' experience of university. This article explores the experiences of 16 students from lower socio-economic backgrounds at one Irish university, with particular reference to peer relationships and their sense of 'belonging'. The research identified the challenges which these students faced in the first few months, including feelings of isolation and 'class–cultural discontinuities'. For one student, from the Traveller community, the transition to university was particularly complex, leading to the 'compartmentalisation' of different elements of her life. The research also, however, highlights these students' positive experiences of university life, which often centred on peer relationships and shared interests and aspirations. Overall, the research points to a diverse range of working-class experiences of university life, and the importance of targeted supports in actively encouraging friendship development in the early stages.